Research in System Reliability and Risk Analysis under development at the Naval Architecture and Ocean Engineering Department from University of São Paulo. Issue 19 (2022) - Abreu, D.T.M.P.; Barraza, J.E.F.; Clavijo, M.V.; Maturana, M.C.; Santos, J.R.; Schleder, A.M.; Martins, M. R
Abstract: This paper explores a subset of the applied research work carried out at the Analysis, Evaluation and Risk Management Laboratory – LABRISCO from the University of São Paulo, which deals with the issue of system reliability and risk analysis from a broad perspective. The researches and results presented refer to asset integrity and management, risk-based inspection, reliability, availability, and maintainability analysis, life extension in oil and gas facilities, and artificial intelligence diagnosis and prognosis.